The Effects of Racialized Poverty on Health and Health Resources in Eastern North Carolina - Brent, Kendra (East Carolina University, 2023)
Structural violence is integrated into the structures of society by means of social, economic, and political factors and aims to prevent marginalized vulnerable populations from meeting their basic needs. While they often intertwine, groups of people are marginalized based on race, gender, and other forms of embodied identity. Reflections of its syndemic and synergistic influence have been implemented into society as conditioned and sustained suffering among populations. Though structural violence affects many factors, the primary focus of this study will be on the limitations based on class status and race in obtaining health care within different geographical districts. Many individuals affected by poverty tend to receive low-quality education, limiting them in their job endeavors and establishing financial constraints. As a result, living conditions tend to be inadequate and food insecurity more prevalent. Because of these conditions, individuals in poverty are more likely to become ill but are unable to seek appropriate medical attention. Moreover, those who do seek medical attention are burdened by medical debt. This is the beginning of a cycle of using these causes to blame the poor for being poor and/or sick. This endless cycle and overlapping factors can be concluded as racialized poverty. Since racialized poverty is structural, there is little hope of providing full solutions. However, this study seeks to achieve recommendations on practices and elements that could be implemented and operationalized to induce less harm than the current systems. Additionally, it will critique organizations designed to help marginalized groups within society obtain healthcare resources.
Keywords: racialized poverty, structural violence, health resources